Automation Architecture based on Cyber Physical Systems for Flexible Manufacturing within Oil&Gas Industry - Marcelo V García; Edurne Irisarri; Federico Pérez; Elisabet Estévez; Marga Marcos (Revista Iberoamericana de Automática e Informática Industrial RIAI)
It is clear that in the next few years most of the technologies involved in the so-called Industry 4.0 will have a deep impact on manufacturing companies, including those related to Oil & Gas exploration and production. Low cost automation promotes reference architectures and development approaches aiming at increasing the flexibility and efficiency of production operations in industrial plants. In this sense, OPC UA, in addition to allowing companies to join the Industry 4.0 initiative, provides local and remote access to plant information, enabling a recognized mechanism for both, horizontal and vertical integration in a reliable, safe and efficient way. The contribution of this article is an open architecture for vertical integration based on cyber-physical production systems, configured under IEC 61499 and using OPC UA, suitable to achieve flexible manufacturing within Oil & Gas industry.